PENYAKIT PEKERJA DALAM KEGIATAN EKSPLOITASI HUTAN DI KALIMANTAN TENGAH - Soenarno Soenarno; Maman Mansyur Idris (Jurnal Penelitian Hasil Hutan, 1988)
Working conditions in  tropical  forests especially  in logging. are generally  difficult.  The  materials  handled  are heavy, outdoor weather  conditions  are unpredicted. the growth  of  vegetation are commonly dense, and temperature and humidity are mostly high.  These  conditions.    together with  inappropriate   workers'   facilities  and   nutrient  will  lead to  bad health conditions   and  occurence  of  various illnesses.An  investigation   carried  out  in  two  logging  companies in Central Kalimantan   revealed  that  there  are 8  kinds  of illnesses  that   are  commonly  suffered  by  workers,   i.e  :   influenza,   malaria, irritation of respiratory systems,  feeling  of nausea, back and neck problems,   headache/giddiness,  sore eyes,  and skin  disease.  The  highest  risk  of  having  illness is for those  working  in  transportation operations,  followed   by  felling,  skidding  and  workshop.   It  is also found   that  the  least risk is timber  cruising activity.